Principles of international water law: creating effective transboundary water resources management. (5th August 2009) - Rahaman, Muhammad Mizanur
This article summarises the principles of international water law related to transboundary water resources management and analyses to what extent these principles are incorporated in recent international conventions and treaties. The study reveals that principle of equitable and reasonable utilisation, obligation not to cause significant harm, principles of cooperation, information exchange, notification, consultation and peaceful settlement of disputes are widely acknowledged by modern international conventions, agreements and treaties. These principles could facilitate effective transboundary water resources management involving riparian countries of shared watercourses and hence, promote sustainable development around the world.